Structural organization of the Helicoverpa zea gene encoding the precursor protein for pheromone biosynthesis-activating neuropeptide and other neuropeptides. - Ma, P W (1994)
Sex pheromone biosynthesis in a number of moth species is induced by a conserved 33-amino acid amidated neuropeptide PBAN (pheromone biosynthesis-activating neuropeptide). We have isolated and characterized the Helicoverpa zea PBAN cDNA corresponding to a 766-nucleotide mRNA that is expressed in the subesophageal ganglion of adult moths. This mRNA is encoded on a transcription unit comprising 6 exons. The longest open reading frame of the cDNA encodes a 194-amino acid precursor protein that contains the PBAN peptide sequence. Proteolytic processing of this protein, which has structural features consistent with its being a preprohormone, is predicted to generate Hez-PBAN and four additional neuropeptides having a common C-terminal pentapeptide motif, Phe-Xaa-Pro-(Arg or Lys)-Leu (Xaa = Gly, Ser, or Thr), which is also found in insect pyrokinin and myotropin peptide families.